Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapters 1-5 Cumulative Review Problem Set - Page 233: 15



Work Step by Step

We will evaluate the expression by first simplifying the expression and then substituting $x=-1$ into the resultant expression: $(x^{2}+2x-4)-(x^{2}-x-2)+(2x^{2}-3x-1)$ =$x^{2}+2x-4-x^{2}+x+2+2x^{2}-3x-1$ =$x^{2}-x^{2}+2x^{2}+2x+x-3x-1-4+2$ =$2x^{2}+3x-3x-5+2$ =$2x^{2}+0-3$ =$2x^{2}-3$ =$2(-1)^{2}-3$ =$2(1)-3$ =$2-3$ =$-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.